Rapid 3D bioprinting of decellularized extracellular matrix with regionally varied mechanical properties and biomimetic microarchitecture. (December 2018) - Ma, Xuanyi; Yu, Claire; Wang, Pengrui; Xu, Weizhe; Wan, Xueyi; Lai, Cheuk Sun Edwin; Liu, Justin; Koroleva-Maharajh, Anna; Chen, Shaochen
Abstract: Hepatocellular carcinoma (HCC), as the fifth most common malignant cancer, develops and progresses mostly in a cirrhotic liver where stiff nodules are separated by fibrous bands. Scaffolds that can provide a 3D cirrhotic mechanical environment with complex native composition and biomimetic architecture are necessary for the development of better predictive tissue models. Here, we developed photocrosslinkable liver decellularized extracellular matrix (dECM) and a rapid light-based 3D bioprinting process to pattern liver dECM with tailorable mechanical properties to serve as a platform for HCC progression study. 3D bioprinted liver dECM scaffolds were able to stably recapitulate the clinically relevant mechanical properties of cirrhotic liver tissue. When encapsulated in dECM scaffolds with cirrhotic stiffness, HepG2 cells demonstrated reduced growth along with an upregulation of invasion markers compared to healthy controls. Moreover, an engineered cancer tissue platform possessing tissue-scale organization and distinct regional stiffness enabled the visualization of HepG2 stromal invasion from the nodule with cirrhotic stiffness. This work demonstrates a significant advancement in rapid 3D patterning of complex ECM biomaterials with biomimetic architecture and tunable mechanical properties for in vitro disease modeling. Graphical abstract: We present a rapid light-based 3D bioprinting process to pattern liver dECM with tailorable mechanical properties to serve as a platform for HCC progression study.